Analisis Strategis Pengelolaan Aset Daerah Berdasarkan Pernyataan Standar Akuntansi Pemerintah No. 7 - Heri Yuliantoro; Hamdani Arifulsyah (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
The purpose of this study was to determine how the removal of damaged and obsolete fixed assets according to the Government Accounting Standards Statement No.7 at the Financial and Asset Management Agency of Bengkalis Regency, Riau Province. Sources of data obtained from interviews and documentation. This research was conducted by comparing the accounting treatments that have been carried out with standards. The results of this study that there are written off assets that have been done need to be adjusted to the standard. Write-off of fixed assets must be accompanied by the elimination of accumulated depreciation of Rp. 1,138,992,230,087. As an improvement, a correction journal needs to be made to remove the accumulated depreciation.